Multidimensional Poverty in Rural Odisha: Moving from Household to Individual - Surya Narayan Biswal, S K Mishra, M K Sarangi (International Journal of Advanced Science and Technology, 2020)
The present study is conducted with the basic objective of assessing Multi-Dimensional Poverty (MDP)through Multidimensional Poverty Index (MPI), both at household and individual level, utilisingAlkira-Foster (AF) Method. The study is conductedacross three villages of Naugoan block of Jagatsinghapur district of Odisha over 150 households comprising 501 individuals. The study observed that more than 75% of households and individuals are deprived in terms of improved sanitation and access to clean cooking fuel. The examination of MPI reveals higher multidimensional poverty at the individual level in comparison to the household level. Further, MPI for females revealed that they are more deprived in comparison to their male counterpart because of theirlow level of education, low freedom in the society and male’s dominance in every aspect of life. MPI across social groups establishedthat SC people are relatively more deprived in comparison to other social groupsin the multidimensionally poor category. Low level of education and health attainment, low social status, bad housing condition, open defecation practice, and access to unhygienic cooking fuel are the primary reasons for higher deprivation of SC people. Lastly, MPI across different occupation showed a high incidence of poverty among farmers, daily labourers and unemployed. Different policies are in implementation in this district by both State and Central Governments to ameliorate poverty and improve the standard ofliving of women, children, farmers and weaker sections like SC and SEBC. The study recommends strict implementation of various policies to realise the objectives of these programmes and help women, farmers, SC and SEBC groups come out of poverty measured in a multidimensional framework.